Historiography and Identity. (Turnhout, Belgium)
4 cilt (x, 377 sayfa)
Keywords: “Historical writing has shaped identities in various ways and to different extents. This volume explores this multiplicity by looking at case studies from Europe, Byzantium, the Islamic World, and China around the turn of the first millennium. The chapters in this volume address official histories and polemical critique, traditional genres and experimental forms, ancient traditions and emerging territories, empires and barbarians. The authors do not take the identities highlighted in the texts for granted, but examine the complex strategies of identification that they employ. This volume thus explores how historiographical works in diverse contexts construct and shape identities, as well as legitimate political claims and communicate ‘visions of community’.” --